In vitro seed germination and seedling growth of Calanthe discolot Lindl. - Bae, Kee Hwa; Oh, Kyoung Hee; Kim, Soo-Young (Plant Breeding and Seed Science, 2015)
We investigated the effects of sodium hypochlorite (NaOCl) and culture medium on embryo swelling and germination of Calanthe discolor Lindl., and established a method for determining the swelling and protocorm formation of C. discolor seeds via in vitro examination of immature seeds. Treatment of immature seeds with NaOCl greatly enhanced the extent of embryo swelling and protocorm formation of immature zygote embryos compared to seeds without NaOCl treatment. The effects of the culture media were also evaluated with regard to embryo swelling and protocorm formation of in vitro cultured seeds with and without NaOCl treatment. Additionally, the effects of white fluorescent light and red and blue LED lights on seedling growth in in vitro culture were examined. The most suitable condition for seedling growth after 12 weeks of culture was the red LED light with POM medium. These results show effective asymbiotic germination and growth of C. discolor.